Orientational changes of the absorbing dipole or retinal upon the conversion of rhodopsin to bathorhodopsin, lumirhodopsin, and isorhodopsin. - Michel-Villaz, M (1982)
The orientational change of the absorbing dipole of the retinal chromophore in vertebrate rhodopsin (rhodo) upon photo-excitation to bathorhodopsin (batho), lumirhodopsin (lumi) and isorhodopsin (iso), has been studied by polarized absorption and linear dichroism measurements on magnetically oriented frog rod suspensions that were blocked at liquid nitrogen temperature. Both the azimuthal component delta theta and the polar component delta theta of the total angular change were studied in separate experiments. Delta theta was estimated from polarized absorption measurements on rods oriented transversally with respect to the analyzing beam. The data show unequivocally that upon the rhodo leads to batho transition, the dipole shifts out of the membrane plane by only few degrees; delta theta congruent to -3 degree. This azimuthal shift was nearly exactly reversed upon the batho leads to lumi decay. A very small shift (delta theta less than or equal to 1 degree) toward the membrane plane was observed upon a rhodo leads to iso conversion. The polar component delta theta of the angular shift was estimated by studying the photoreversion of linear dichroism induced by photo-excitation with polarized light in rods oriented parallel to the analyzing beam. Upon the rhodo leads to batho transition, ther was a shift delta theta = 11 +/- 3 degrees. The overall angular shift upon this first photo-exciting step, which corresponded to the isomerisation of retinal, was only delta omega = 11 +/- 3 degrees. This is smaller than what may be expected for a cis-trans isomerization of a retinal molecule with one end fixed, and different from what has been previously estimated by another group. These discrepancies are discussed.